Tradisi 7 Bulanan dalam Suku Batak Toba dan Suku Karo di Desa Tanjung Morawa - Ricardo Simanullang; Ardy Putra Purba; Raymond Simamora; Abd Haris Nasution; Tappil Rambe; Syahrul Nizar (Departement of Mathematics Education, 2024)
Wedding ceremonies have diversity and variations according to the customs that apply in each tribe including the Toba Batak tribe and batak karo. The marriage ceremony that has been carried out will bind a household that will later want the presence of the child as the successor of the offspring. This study aims to find out one of the traditions of Batak Toba and Karo about 7 monthly or commonly referred to in Batak Toba mambosuri and in Karo mbesur-besuri. With this study to find out the differences and similarities about 7 months in the two tribes. The method used in writing this article is using qualitative methods, interviews, and observations. The theories used are symbolic interaction theory, social systems theory, and change theory. The results of this study can be concluded that it is concluded that, the traditional tradition of mbesur-mbesuri in the community with the implementation of traditional mbesur-mbesuri tardisi by hoping that prospective mothers and children will get safety and tranquility before entering the time of birth (Darwin Prints, 2004) with the encouragement that becomes a motivation in carrying out traditional tardisi for pregnancy with aspects of old beliefs and promidial aspects. Likewise with the Toba Batak custom, it is hoped that children and mothers will survive during childbirth. This 7-monthly event is a prayer letter for new families, married and will become mothers and fathers later after the child is born.